Aspirant Sport Professionals' Perceptions of Leader Political Stances in the Workplace: An Exploratory Investigation - Marshall Magnusen; Matt Robinson (Journal of Applied Sports Management, 2024)
The purpose of this exploratory study was to better understand how political behaviors by a sport organization’s leader impact aspirant sport professionals. This qualitative study utilized criterion-based and snowball sampling methods to gather data from 202 aspirant sport professionals (46.5% male, 53.5% female). Participants were given a hypothetical employment scenario and responded to four questions regarding how a leader’s political behavior might impact their feelings, thoughts, and behaviors toward the sport employer. Utilizing thematic analysis, the following themes were discovered: Discomfort and Indifference (Question 1), Expectancy Violation and Power Divide (Question 2), Visceral Thinking and Calculated Thinking (Question 3), as well as Reconciliation and Balance and Withdrawal (Question 4). Though sport leagues and sport leaders taking political stances has become more commonplace in recent years, the current results provide evidence that this shift may not be beneficial to sport employers as they look to recruit and retain high-quality personnel.
Keywords: job seekers; organizational behavior; management; political skill; thematic analysis